PERBANDINGAN STRATEGI KONSELING ISLAM DENGAN PSIKOTERAPI BARAT: PENDEKATAN TEORITIS DAN PRAKTIS - Febriansyah, Agung Dwi; Rostiawan, Fitra Fajar; Arifrianto, Febri; Mujidin, Mujidin (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This research aims to analyze the comparison between Islamic counseling and Western psychotherapy from theoretical and practical perspectives in supporting the mental, emotional, and spiritual well-being of individuals. Using a literature review approach, relevant sources such as scientific articles, books, and academic publications that examine the concepts, methods, and applications of both approaches are analyzed. Islamic counseling is rooted in spiritual values derived from revelation (Al-Qur'an and Hadith), employing techniques such as muraqaba, dhikr, prayer, and spiritual reflection. This approach offers holistic solutions that are relevant to Muslim individuals, particularly in cultural and religious contexts. Conversely, Western psychotherapy is based on the principles of empiricism and humanism, focusing on the development of individual potential and adaptation to psychological challenges through scientific methods such as psychoanalysis, cognitive-behavioral therapy, and mindfulness-based interventions. Despite fundamental differences in philosophy and methods, both approaches share the same goal of enhancing individual well-being. This study also identifies the potential for integrating these two approaches by combining the spiritual strengths of Islamic counseling with the scientific framework of Western psychotherapy to create more inclusive and holistic solutions. Such integration is relevant in modern pluralistic societies to address complex issues such as anxiety, depression, and identity disorders while respecting clients' spiritual and cultural values format.